Entre a opinião e o público: linguagens políticas na independência e no primeiro reinado do Brasil - Vianna, Jorge Vinicius Monteiro (2019)
The present thesis aims to analyze the image First Reign of Brazil, especially the model built in the nineteenth century, as a period marked by crises and instability. The object of analysis was the features of the political languages developed from the Independence period until the First Reign. The documents chosen consisted of circumstantial political periodicals that circulated in the Rio de Janeiro Court and in the provinces of São Paulo and Minas Gerais, between the years of 1821 and 1829. For the exploration of the press, the Collinwoodian perspective of the Cambridge School was adopted, which identifies the importance of languages and political vocabulary in the political context. From their various nuances, we select the authors that reinforce the necessary articulation between text and context, because it opens the possibility to understand what each author aimed at formulating or answering a certain question, or why it challenges, repels, privileges or ignores certain sociopolitical perspectives and interpretations. The theoretical basis was the concepts of public opinion, public spaces, nation and political culture for the understanding of the circulation of ideas during the process of enchainment and animosities around liberal political discourses, which, published in Portuguese America since 1821, formed, forged and legitimated the moderate liberal political language created in the First Reign. Finally, we sustain as research conclusion two hypotheses. The first consists in the affirmation of moderate liberal language as a process of linguistic reordering and resignification of contents formulated in enunciative structures already circulating during Brazil's process of political emancipation. The second emphasizes the moderate liberal language as a new discursive form of making opposition to the imperial government of d. Pedro I.